Experimental field evidence of common pool resources: The Water Judge in Bolivia - Javier Aliaga Lordemann (Institute for Advanced Development Studies (INESAD), 2021)
Common pool resources (CPRs) are usually exploited one generation after another - often overexploited - meaning there is an intergenerational link between the consumers - e.g., water for farming activities. This key dimension is often not considered in theoretical or field experiments, due to the difficultly in approaching it. We want to overcome this barrier introducing the hypothesis of ''intergenerational altruism" for CPRs. The implication is that altruism reduce the exploitation of the natural resources, since the agents recognize that the exploitation not only creates negative externalities for their own generation, but also for all future generations. An alternative hypothesis is the ''intergenerational equity'' where the agents restrain their consumption to equalize their income over time. To prove these hypotheses, we conducted a field experiment in four farming communities located in the Bolivian Department of Chuquisaca during the third quarter of 2019. We consider common water for farming activities as a CPRs, since these communities use this resource for several decades, the intergenerational link is evident. Our intergenerational field experiment includes four treatments based on the replacement rate of the resources - i.e., FAST, SLOW, RESTART or normal replacement, under one-shot non-cooperative game without feedback. We also introduce two variations, the possibility to accumulate water in a dam, which modify the availability of CPRs. Second, the possibility to manage the common farming water through the traditional social arrangement of the Water Judge, which is a representative member of the community delegated to solve problems related with water management, named SAT treatment. The results showed that our hypothesis was not probed since the intergenerational link does not mitigate the overexploitation of CPRs. Nevertheless, we also found that the "Water Judge" could be a cost-effective treatment in small farming communities.
Keywords: C72; C92; D62; Q20; 330; Common pool resources; intergenerational altruism and equity; free riders